Analisis Respon Negatif Publik terhadap Putusan MK Nomor 90/PUU-XXI/2023 dan Dampaknya terhadap Peran Presiden dalam Sistem Kelembagaan Pemerintahan Indonesia - Farhan, Mochammad; Uu Nurul Huda (Universitas Muhammadiyah Kotabumi, 2024)
Decision of the Constitutional Court (MK) Number 90/PUU-XXI/2023 on the change in the minimum age requirement for presidential and vice-presidential candidates has generated various responses from the Indonesian people. This research aims to analyse the public response to the decision and its its impact on the role of the President in the institutional system of the Indonesian government and public participation in democracy. and public participation in democracy. Based on a descriptive study with a juridical-normative approach, the results of the study show that the majority of the public who gave a negative response to the verdict had concerns about the integrity of the judiciary and the potential for dynastic politics. In addition, the Court's decision introduced a new dynamic in the relationship between the executive and judiciary that affects the position and role of the President. Although Nonetheless, the decision also increased political awareness and political awareness and public participation, albeit accompanied by a decline in trust in the Constitutional Court. Overall, the judgement creates an opportunity for institutional reform that can strengthen Indonesia's democracy and promote transparency. institutional reforms that can strengthen Indonesia's democracy and promote transparency and accountability in political decision-making. accountability in political decision-making. Keywords: Public response; Constitutional Court; Role of the President; System of government; Indonesian democracy.